Cost-Effective analysis of silver diamine fluoride in comparison to glass ionomer cement along with fluoride varnish in the management of early childhood caries in anganwadi centers of Mangalore: A randomized control trail - Prakash Babu Kodali; Vijaya Hegde; Rasheed Minhaz; P Prasanna Mithra; Shubhan Alva; Joe Joseph; Roshni R S (Journal of Indian Association of Public Health Dentistry, 2022)
Introduction: Early childhood caries (ECC) is a major public health challenge affecting preschool children. Silver diamine fluoride (SDF) is a noninvasive, alternative method to surgical intervention in the treatment of ECC. It has also shown to inhibit the development of new carious lesions. Materials and Methods: An open-labeled randomized controlled trail was conducted among 200 Anganwadi children. They were divided into two groups: Group A received oral prophylaxis and application of 38% SDF and Group B received oral prophylaxis, restoration using glass ionomer cement (GIC) and application of 5% sodium fluoride varnish (FV). The effectiveness in reduction of dental caries was assessed based on its ability to result in a positive outcome postintervention. Cost-effectiveness analysis, from the service provider perspective, was conducted to evaluate the effectiveness of SDF when compared to GIC followed by the application of FV. Average cost-effectiveness ratio and incremental cost-effectiveness ratio (ICER) for all the specific outcomes were assessed. Results: The average cost for converting an individual tooth from active caries to inactive caries using SDF was 67.30 Indian Rupees (INR), whereas the same was 225.5 INR using GIC with FV. The ICER of the interventions for the total number of inactive caries postintervention was measured at −89.9, implying that Incremental costs of one extra tooth of active caries to be converted into inactive caries using SDF will cost 89.9 INR less compared to the same outcome using GIC with FV. Conclusions: Thus, the study showed that SDF was cost-effective when compared to GIC in restoring active carious lesions.